WIDODO SUTIYO: PENGABDIAN TIGA DEKADE UNTUK NEGARA DAN BANGSA - Harnowo, Eko (Kementerian Sekretariat Negara Republik Indonesia, 2014)
A year has elapsed since the passing of Widodo Sutiyo on 13 October 2013. Widodo was formerly a career diplomat who later served as the official interpreter and translator of the President of the Republic of Indonesia for three decades (1968-1998). During thirty years, he played an irreplaceable role in bridging the communication between the late President Soeharto with his international counterparts, and in articulating the policies of the Government of the Republic of Indonesia to the international community. Therefore, his excellence in performance and longevity of dedication should be truly appreciated and be a source ofinspiration to present and future Indonesian interpreters and translators. In the memory of the late Widodo Sutiyo, this article will shed a light on his work performance, dedication, and challenges he had to address in the field of translation and interpretation in the service of the state and nation.